Existência de soluções não-negativas para uma classe de problemas semilineares elípticos indefinidos - Costa, Gustavo Silvestre do Amaral (2017)
In this work we will discuss the existence of nonnegative solutions for a class of indefinite semilinear elliptic problems: (Pμ)   − u = λ1u+μg(x,u)+W(x)f(u), em u = 0 , sobre ∂ , where is a bounded smooth domain in RN, N ≥ 3, μ is a nonnegative parameter, λ1 is the first eigenvalue of the operator − under Dirichlet boundary conditions, W ∈ C(¯ ,R) is a weight function, f ∈ C(R,R), and g : ¯ ×R→R is a Carathéodory locally bounded function, i.e, for every s0 > 0, there is M := M(s0) > 0 such that |g(x,s)| ≤M for 0 ≤ |s| ≤ s0 and for almost every x ∈ ¯ .